2018
DOI: 10.1038/s41598-017-18645-8
|View full text |Cite
|
Sign up to set email alerts
|

Flavin Reductase Contributes to Pneumococcal Virulence by Protecting from Oxidative Stress and Mediating Adhesion and Elicits Protection Against Pneumococcal Challenge

Abstract: Pneumococcal flavin reductase (FlaR) is known to be cell-wall associated and possess age dependent antigenicity in children. This study aimed at characterizing FlaR and elucidating its involvement in pneumococcal physiology and virulence. Bioinformatic analysis of FlaR sequence identified three-conserved cysteine residues, suggesting a transition metal-binding capacity. Recombinant FlaR (rFlaR) bound Fe2+ and exhibited FAD-dependent NADP-reductase activity, which increased in the presence of cysteine or excess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 91 publications
0
8
0
Order By: Relevance
“…Previously we found TF in the CW fraction of S. pneumoniae 27 , 28 . Notably, we recently showed that a bona fide cytoplasmic protein, malonyl-CoA:ACP transacylase (FabD), which is involved in lipid metabolism could not be found in the CW protein extract 28 , 33 . To further verify that TF is indeed CW-localized, a monoclonal anti-rTF antibody was incubated with a live unencapsulated, serotype 2-derived, R6 strain and flow cytometry analysis was performed.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously we found TF in the CW fraction of S. pneumoniae 27 , 28 . Notably, we recently showed that a bona fide cytoplasmic protein, malonyl-CoA:ACP transacylase (FabD), which is involved in lipid metabolism could not be found in the CW protein extract 28 , 33 . To further verify that TF is indeed CW-localized, a monoclonal anti-rTF antibody was incubated with a live unencapsulated, serotype 2-derived, R6 strain and flow cytometry analysis was performed.…”
Section: Resultsmentioning
confidence: 99%
“…The untagged rTF protein was commercially produced by Protein laboratories, Ltd. (Israel), which amplified tig from TIGR4 genome 69 , and cloned, expressed and purified the protein as previously described 28 , 33 . Validation was also performed by the company using MS.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Riboflavin is an essential precursor of compounds such as the flavin mononucleotide (FMN) and flavin adenine dinucleotide (FAD) that are cofactors of flavoproteins. Flavoproteins have pleiotropic functions [42] and have been implicated in the oxidative stress response in several anaerobes [43,44]. In C. difficile, flavoproteins are overrepresented in the regulon of the general stress response sigma factor σB [45,46] and have been implicated in spore resistance [47].…”
Section: Autofluorescence Is Independent Of Sigb and Spo0amentioning
confidence: 99%
“…Flavoproteins act as electron transfer proteins and mediate redox reactions, for instance in the metabolism of carbohydrates, oxidative stress response or even in the extracellular environment (Garcia-Angulo 2017). In Streptococcus pneumoniae, the flavin reductase FlaR contributes to the resistance to H2O2 [43]. The expression of genes involved in the synthesis and uptake of flavins is regulated through FMNdependent riboswitches [56,57].…”
Section: Microscopy Of C Difficile 630δerm Cells During Different Stages Of Cell Growthmentioning
confidence: 99%